Long-term results from the Italian real-world experience on obeticholic acid treatment in primary biliary cholangitis: The RECAPITULATE study. (March 2023) - Terracciani, F.; De Vincentis, A.; D'Amato, D.; Invernizzi, P.; Morgando, A.; Vanni, E.; Viganò, M.; Alvaro, D.; Venere, R.; Lleo, A.; Colapietro, F.; Degasperi, E.; et al.
Abstract : Introduction: Obeticholic acid (OCA) is the only licensed second-line therapy for PBC patients non-responders/intolerant to UDCA. Real-world experiences on OCA therapy are somehow limited by reduced sample sizes and short follow-up. Aim: Aim of the RECAPITULATE study is to provide long-term real-world data on OCA therapy in a large Italian cohort of patients with PBC. Methods: Data on patients in OCA therapy from centres belonging to "Italian PBC registry", "CLEO/AIGO", "Sicilian PBC Network" and "PBC Project Piemonte-Liguria-Valle-D'Aosta" were captured. Cumulative incidences of OCA response and discontinuation were evaluated through Aalen-Johansen (taking into account the competing risk of discontinuation) and Kaplan-Meier estimators, respectively. Results: 441 PBC patients (median age 58, women 88%) on OCA therapy for at least 6 months were enrolled from 50 Italian centres, with a median time on OCA therapy of 24 months (IQR 12-36, max 48). Cirrhotics were 152 (34%), PBC/autoimmune hepatitis (AIH) overlap were 59 (13%). According to POISE, response probabilities were 37.5/43.5/47.2% at 12/24/36 months. Discontinuation probabilities were 12.8/17.7/22.9% at 12/24/36 months, with pruritus (41 patients, 48%) and hepatic events (18 patients, 21%) as leading causes. In cirrhotics, probabilities of response were lower (25.9/27.7/34.8% at 12/24/36 months; p<0.01 Vs non-cirrhotics), due to higher discontinuation rates (19.9/27.6/34.6% at 12/24/36 months; p<0.01 Vs non-cirrhotics), while patients with PBC/AIH overlap did not show significantly different probabilities of response and discontinuation (p=0.20). Results of Vibration-Controlled-Transient-Elastography (VCTE) were available from 309/114/69 patients at 0/12/24 months. Liver stiffness measurement (LSM) was stable at 12 months in both OCA responders and non-responders, while a significant reduction was observed at 24 months only in responders (p=0.01). Conclusions: Our results confirm long-term efficacy and safety of OCA therapy in a large real-world cohort of PBC patients. These first results concerning LSM variation over time under OCA treatment need to be confirmed in a larger subgroup of patients.